Experimental and density functional theory investigations of catechol sensing properties of ZnO/RGO nanocomposites - Ponnusamy, Rajeswari; Venkatesan, Rajiu; Gangan, Abhijeet; Samal, Rutuparna; Chakraborty, Brahmananda; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2019)
Catechol, an essential industrial feedstock is one of the major environmental pollutant which causes several health issues including skin irritation, eye damage and genetic defects. In this work, we have investigated the catechol sensing performance of ZnO/RGO composites for its quantitative detection. ZnO/RGO composite showed superior electron transfer kinetics, sensitivity (162.04 mu A mM cm(-2)) and lower detection limit (47 nM) than that of bare ZnO nanoparticles. Further, the change in the zeta potential towards the lower negative demonstrated the strong electrostatic interaction between ZnO-RGO and catechol where it is converted as 1, 2 Benzoquinone through redox reactions. By using state of the art of Density Functional Theory simulations, we have demonstrated the interaction of catechol molecule on various ZnO clusters and RGO supported ZnO clusters. The strong bonding between p orbital of O atom of catechol and d orbital of Zn atom and its charge transfer facilitate the oxidation of catechol molecule. In the presence of RGO, the binding energy of catechol and charge transfer increases which qualitatively infer that RGO/ZnO exhibits higher sensitivity compared to bare ZnO and in consistency with the experimental observations.